Effect of subinhibitory concentrations of antibiotics on the adhesion of Streptococcus pyogenes to pharyngeal epithelial cells. - Tylewska, S (1981)
The hydrophobicity and charge of the cell surface of M protein-positive (M+) and the less virulent M protein-negative (M-) strains of type 12 Streptococcus pyogenes have been studied, respectively, by hydrophobic interaction chromatography and free zone electrophoresis. The M+ strain had a more hydrophobic and a more negatively charged surface than the M- strain. When the M+ strain was cultivated in the presence of sub-minimum inhibitory concentrations of different antibiotics, its hydrophobicity either decreased or did not change. The M+ organisms adhered to pharyngeal epithelial cells more avidly than M+; however, cultivation of both strains with sub-minimum inhibitory concentrations of penicillin and rifampin led to the decrease in adhesion. Tetracycline caused a decrease in adhesion for the M+ strain only, whereas cephalothin and polymyxin (to which the strains are resistant) did not affect adhesion or hydrophobicity of the M+ organisms. The negative surface charge of the M+ bacteria increased considerably upon exposure to rifampin and penicillin, and the M- bacteria exhibited small or no change. The contributions of these changes to suppression of infections are discussed.